Characterization of difenoconazole resistance in Lasiodiplodia theobromae from papaya in Brazil. Issue 4 (20th December 2019) - Li, Yuan; Tsuji, Susan Satie; Hu, Mengjun; Câmara, Marcos Paz Saraiva; Michereff, Sami Jorge; Schnabel, Guido; Chen, Fengping
Abstract: BACKGROUND: Stem‐end rot caused by Lasiodiplodia theobromae is one of the most important diseases of papaya in northeastern Brazil. It can be controlled effectively by demethylation inhibitor (DMI) fungicides, but the occurrence of DMI resistance may decrease fungicide efficacy. RESULTS: Detached fruit studies revealed that isolates with EC50 values of 6.07 and 6.28 μg mL −1 were not controlled effectively, but reduced virulence and ability to grow at temperatures ranging from 12 to 32 °C suggesting fitness penalties were observed. Cross‐resistance was observed only between difenoconazole and propiconazole. The entire cytochrome P450 sterol 14α‐demethylase (Lt CYP51 ) gene and its flanking regions were cloned. The gene was 1746 bp in length and contained three introns. The predicted protein contained 525 amino acids. Phylogenetic tree analysis showed that the Lt CYP51 belongs to the CYP51B clade. No amino acid variation was found between sensitive and resistant isolates; however, the gene was constitutively more highly expressed in resistant isolates. CONCLUSION: Resistance to DMI fungicides in L. theobromae is based on Lt CYP51 gene overexpression and fitness penalties may be present in difenoconazole‐resistant isolates. © 2019 Society of Chemical Industry Abstract : Stem‐end rot caused by Lasiodiplodia theobromae is one of the most important diseases of papaya in northeastern Brazil. It can be controlled effectively by demethylation inhibitor (DMI) fungicides, but occurrence of DMI resistance may decrease fungicide efficacy.